Qualitative Characteristics of Suffix Sets in Derivatives from Interjections in the Semantic-Field Dictionary of the Slovenian Language for Entries in B - Stramljič Breznik, Irena (Slavia Centralis, 2024)
The present paper focuses on the qualitative analysis of suffix sets in derivatives from interjections based on the material from the Semantic-Field Dictionary of the Slovenian language for Entries in B. The purpose of the analysis is to determine which semantic groups of word formations follow each other within the most common two-, three- or rare four-suffix sets. Although the sample is small, the analysis shows that at the level of suffix combinations and the strength of the semantic sequence of word formations, some of the two and three-suffix sets are recognized as productive word-formation models of derivatives from interjections, as they also occur in wider linguistic use, as reflected in the metaFida corpus.